Women art workers and the arts and crafts movement - Thomas, Zoë (Gender in history, 2020)
Front matter -- Contents -- Figures -- Acknowledgements -- Introduction -- Clubhouses and guild halls -- Exhibiting the Arts and Crafts -- 'At Home' in artistic houses and studios -- 'Artistic' businesses and 'medieval' workshops -- Out of the guild hall and into the city -- Epilogue -- Select bibliography -- Index